Integrated cell engineering and scale-up of a non-PGM bifunctional electrocatalyst for durable AEM water electrolysis - Singh, Kailash; Kavitha, T.; Selvaraj, Kaliaperumal (Sustainable Energy & Fuels, 2026)
Developing a scalable and sustainable non-Platinum Group Metal (non-PGM) bifunctional electrocatalyst for Anion Exchange Membrane (AEM) water electrolyzers remains a significant challenge, particularly at industrially relevant scales. Most reported non-PGM catalysts are demonstrated on small electrode areas (typically <= 2 cm(2)), making scalability a major bottleneck. Issues such as achieving uniform catalyst coating, maintaining similar structural morphology, and preventing activity loss due to leaching become increasingly prominent at larger scales. Therefore, a Nickel Copper Phosphide-Nickel Sulphide (NCP-NS) catalyst was developed and successfully scaled-up to >10 cm(2) electrode active area, and its performance was evaluated in an electrolyzer cell. A larger 13 cm(2) AEM cell was developed by addressing key parameters: (i) electrode design (mass loading density), (ii) assembly conditions (torque and gasket thickness), (iii) operational parameters (flow rate and temperature), and (iv) engineering aspect measurements (Fujifilm pressure distribution and interfacial contact resistance). These optimizations resulted in a high current density of 1012 mA cm(-2) at 2 V, with the stack maintaining 98% of its performance after 100 hours of continuous operation. The electrocatalysts delivered 55.96 kWh kg(-1) energy efficiency at 2 V. This work demonstrates how systematic scale-up and cell engineering can bridge the gap between lab-scale innovation and commercial application.